Tumor biology of non-metastatic stages of clear cell renal cell carcinoma; overexpression of stearoyl desaturase-1, EPO/EPO-R system and hypoxia-related proteins - Stoyanoff, Tania Romina; Rodríguez, Juan Pablo; Todaro, Juan Santiago; Espada, Joaquín Diego; Melana Colavita, Juan Pablo; Brandan, Nora Cristina; Torres, Adriana Mónica; Aguirre, María Victoria (Springer, 2016)
Clear cell renal cell carcinoma (ccRCC) is the most common subtype of renal carcinoma. There is great interest to know the molecular basis of the tumor biology of ccRCC that might contribute to a better understanding of the aggressive biological behavior of this cancer and to identify early biomarkers of disease. This study describes the relationship among proliferation, survival, and apoptosis with the expression of key molecules related to tumoral hypoxia (hypoxiainducible factor (HIF)-1α, erythropoietin (EPO), vascular endothelial growth factor (VEGF)), their receptors (EPO-R, VEGFR-2), and stearoyl desaturase-1(SCD-1) in early stages of ccRCC. Tissue samples were obtained at the Urology Unit of the J.R. Vidal Hospital (Corrientes, Argentina), from patients who underwent radical nephrectomy for renal cancer between 2011 and 2014. Four experimental groups according to pathological stage and nuclear grade were organized: T1G1 (n = 6), T2G1 (n = 4), T1G2 (n = 7), and T2G2 (n = 7). The expression of HIF-1α, EPO, EPO-R, VEGF, VEGFR-2, BclxL, and SCD-1 were evaluated by immunohistochemistry, Western blotting, and/or RT-PCR. Apoptosis was assessed by the TUNEL in situ assay, and tumor proliferation was determined by Ki-67 immunohistochemistry. Data revealed that HIF-1α, EPO, EPO-R, VEGF, and VEGF-R2 were overexpressed in most samples. The T1G1 group showed the highest EPO levels, approximately 200 % compared with distal renal tissue. Bcl-xL overexpression was concomitant withtheenhancementofproliferativeindexes.SCD-1expression increased with the tumor size and nuclear grade. Moreover, the direct correlations observed between SCD-1/ HIF-1α and SCD-1/Ki-67 increments suggest a link among these molecules, which would determine tumor progression in early stages of ccRCC. Our results demonstrate the relationship among proliferation, survival, and apoptosis with the expression of key molecules related to tumoral hypoxia (HIF1α, EPO, VEGF), their receptors (EPO-R, VEGFR-2), and SCD-1 in early stages of ccRCC.
Keywords: Clear cell renal cell carcinoma (ccrcc); Erythropoietin (epo); Epo receptor (epo-r); Apoptosis; Stearoyl desaturase-1 (scd-1)